Green low-carbon phosphogypsum coagulant as well as preparation method and application thereof
The green low-carbon phosphogypsum coagulant prepared by using phosphogypsum waste residue, aluminum ash and potassium carbonate waste residue, the problem of long settling time and low strength when used in cement is solved, and the cement strength is improved and the coagulation speed is accelerated. At the same time, it promotes the efficient utilization of solid waste resources and the achievement of environmental protection goals.
Patent Information
- Application Number
- CN202411702855.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-28
AI Technical Summary
Phosphate gypsum has technical defects such as long settling time, reduced strength and insufficient dosage when used in cement, resulting in low resource utilization, and secondary pollution and high energy consumption during the treatment process.
A green low-carbon phosphogypsum coagulant is prepared by using phosphogypsum waste residue with aluminum ash and potassium carbonate waste residue as raw materials, and a mixture rolling and stirring and stacking activation and maintenance process. This coagulant can accelerate the coagulation and hardening process of phosphogypsum and improve the strength and coagulation speed of cement.
This green low-carbon phosphogypsum accelerator can significantly shorten the settling time of cement, improve the early strength of cement, reduce the water leakage of cement, and improve the service life of concrete. At the same time, it achieves efficient utilization of solid waste resources and avoids secondary pollution and carbon emissions.
Smart Images

Figure BDA0005154043370000091 
Figure BDA0005154043370000101 
Figure BDA0005154043370000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste resource utilization, and in particular to a green low-carbon phosphogypsum coagulant, a preparation method and application thereof. Background Art
[0002] Carrying out comprehensive utilization of bulk industrial solid waste is an important part of the in-depth implementation of the sustainable development strategy, and is of great significance to improving the efficiency of comprehensive resource utilization, improving environmental quality, and promoting the comprehensive green transformation and development of the social economy. Accelerating the research on innovative resource utilization of phosphogypsum, broadening the ways to utilize phosphogypsum resources, and significantly improving the comprehensive utilization capacity of phosphogypsum by 2025, and continuously expanding the scale of utilization, is of great significance to ensuring food production security.
[0003] As we all know, phosphogypsum is the waste residue and phosphogypsum discharged in the process of producing phosphate fertilizer. The production of 1 ton of phosphate fertilizer produces about 5 tons of phosphogypsum. The main chemical component of phosphogypsum is CaSO4·2H2O, and its mass fraction can reach more than 85%. Phosphogypsum has poor crystal form, many harmful impurities, large quality fluctuations, and contains a small amount of soluble P2O5 and fluorine, which causes the cement setting time to be longer, as well as technical defects such as reducing cement strength.
[0004] At present, the global stockpile of phosphogypsum is about 6 billion tons, with an additional 150 million tons per year. The degree of resource utilization of phosphogypsum varies greatly in different countries, among which developed countries started the resource utilization of phosphogypsum earlier. However, the resource utilization rate of phosphogypsum in many countries is still very low. Most of them are stored or discharged into the ocean abroad. In recent years, phosphogypsum has been studied as a cement retarder, mine filling and ecological restoration material, road building material, soil conditioner, gypsum-based material, washed gypsum, heat-treated gypsum, sulfuric acid production, chemical filler, ball milling treatment, chemical treatment, etc., but these treatments more or less have secondary pollution to the environment and unsatisfactory quality, increase energy and resource consumption, increase carbon emissions, increase production and processing costs, and the effect of phosphogypsum treated is still not ideal. The use of cement retarder still leads to technical defects such as long cement setting time, reduced cement strength and low dosage.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a green low-carbon phosphogypsum coagulant and a preparation method and application thereof. The present invention uses waste phosphogypsum and solid waste aluminum ash discharged from the production of aluminum materials by the aluminum industry and solid waste potassium carbonate slag discharged from the production of potassium carbonate products by chemical companies as raw materials to process a green low-carbon phosphogypsum coagulant. The coagulant can improve cement strength and shorten setting time.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] The first aspect of the present invention provides a green low-carbon phospho-gypsum coagulant, wherein the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0009] Phosphogypsum waste slag 95% to 98%, aluminum ash 1% to 4% and potassium carbonate waste slag 1% to 4%.
[0010] The present invention uses waste slag phosphogypsum and solid waste aluminum ash (containing about 61% of aluminum content) discharged from the production of aluminum materials by the aluminum industry and solid waste potassium carbonate slag (containing about 3.8% of potassium content) discharged from the production of potassium carbonate products by chemical companies as raw materials to process into a green low-carbon phosphogypsum coagulant product. A certain amount of aluminum ash and potassium carbonate slag are added to the phosphogypsum to reduce the solubility and P2O5 and fluorine content in the phosphogypsum, and accelerate the nucleation and crystallization speed of the hydration product of the phosphogypsum, thereby accelerating the coagulation and hardening process of the phosphogypsum and accelerating the hydration speed.
[0011] Studies have shown that phosphogypsum containing a certain amount of aluminum ash and potassium carbonate waste residue is more likely to form phosphogypsum cementitious crystals. Storage and curing for a certain period of time will increase the drying and dehydration of phosphogypsum. The alternation of dry and wet will further enhance the volume stability of the hardened phosphogypsum, change the chemical composition and fluorine content of P2O5, and change the characteristics of phosphogypsum with shortened setting time and high strength, thereby making the green low-carbon phosphogypsum coagulant more active.
[0012] The coagulant prepared by the present invention is directly added to cement products, which accelerates the cementing speed and shortens the setting time of cement, with the initial setting time being 105-185 minutes and the final setting time being 195-270 minutes. With the addition of the phosphogypsum coagulant, the hydration strength of the cement is rapidly increased by 7.7-14.5 MPa. The phosphogypsum coagulant reacts with materials such as cement clinker to generate rigid hexagonal strip potassium gypsum (K2SO4·CaSO·H2O) crystals, and potassium sulphur aluminium gypsum overlaps each other to form cement for rapid coagulation, thereby improving the early and late strengths of cement, significantly changing the morphology of cement particle hydration products, increasing the compatibility of cement rheological properties and the compatibility of cement particles with water reducing agents, thereby increasing the specific surface area of cement hydration products by tens to hundreds of times, and these hydration products adsorb the water reducing agent better than cement itself, so that it plays a water reducing role, and also have good water retention, thereby reducing the water seepage of cement. The cement-prepared concrete product produced by using the phosphogypsum coagulant of the present invention has the characteristics of high strength, strong durability and carbonization resistance; compared with the cement produced by natural gypsum, the 28-day compressive elastic modulus of the product of the present invention is lower than that of natural gypsum, especially in the first 3 days, and the 28-day cracking modulus can be reduced by 28%, thereby improving the service life of cement concrete.
[0013] Preferably, the particle size of the phosphogypsum waste residue is 10-50 um; the particle size of the aluminum ash is 10-30 um; and the particle size of the potassium carbonate waste residue is 5-20 um.
[0014] The second aspect of the present invention provides a method for preparing the above-mentioned green low-carbon phospho-gypsum coagulant, the preparation method comprising the following steps:
[0015] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0016] (b) rolling and stirring the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphate gypsum coagulant.
[0017] In the preparation method of the present invention, phosphogypsum is mixed, rolled, stirred and bonded with another material, which will lose crystal water or part of the crystal water and become anhydrous gypsum or hydrated gypsum, and the originally dispersed particles are connected into a whole by the action of chemical water, and the mixed aggregates can be bonded together at the same time. The dehydration environment and dehydration speed of gypsum can greatly affect the crystal density and crystal type of the formed product. If the phosphogypsum is stripped of part of the crystal water, and the critical crystals are kept in the dehydration of phosphogypsum for a certain period of time, so that the phosphogypsum is in a quasi-crystalline non-crystalline state, the newly formed crystals have the opportunity to fully develop and grow, and the density of the new crystals is high, otherwise, the density of the new crystals is low. If the phosphogypsum is placed in a mixed rolling and stirring environment, or dehydrated in a rolling mixed environment under the action of new friction crystal seeds, and dehydrated at a relatively low speed, not only can dense crystals be formed, but also the structural types are different, such as dense hexagonal crystals.
[0018] In addition, the bonding of phosphogypsum with aluminum ash and potassium carbonate waste residue only relies on adsorption. If aluminum ash and potassium carbonate waste residue form another ion group with gypsum, or are in the gypsum lattice, they can form a certain physical and chemical bond with the aggregate, which can make the activation ability stronger to a certain extent. For this reason, the product made by mixing and rolling the aluminum ash and potassium carbonate waste residue by utilizing the particle dispersibility of phosphogypsum is a green low-carbon phosphogypsum coagulant product that combines phosphogypsum with aluminum ash and potassium carbonate waste residue by mixing, rolling, stirring and bonding. It is directly related to whether the green low-carbon phosphogypsum coagulant product can finally meet the technical performance of the product. Through research, it was determined that the rolling force is 3-5 MPa, the stirring speed is 200-208 revolutions per minute, and the rolling force and stirring speed are 2-3 minutes, so as to meet the requirements of sufficient mixing and bonding of green low-carbon phosphogypsum accelerator products, uniform particles, and sufficient hydration of internal substances. The newly generated crystals have the opportunity to fully develop and grow. The alternating rolling and stirring further enhances the volume stability of the hardened body of the green low-carbon phosphogypsum accelerator product, changes and reduces the chemical stability of P2O5, forms the characteristics of short setting time and high strength, and then forms the new crystal density of the green low-carbon phosphogypsum accelerator product. More active. In this product composed of complex microstructures, there are hydration of aluminum and sulfur, hydration of potassium and sulfur, hydration of aluminum and potassium, and substitution of different ion groups during the stacking activation hardening stage. For example, aluminate enters the gypsum lattice to replace sulfate, or enters the alumina lattice to replace sulfate, thus forming an extremely complex microscopic group. There is a dehydration process in stacking activation curing, but the dehydration activation curing temperature and time are different. The main thing to grasp is the activation of the activity of gypsum. According to the law of gypsum dehydration, the most obvious signs are setting time and strength. Therefore, designing a certain process to produce soluble green low-carbon phospho-gypsum accelerator products can make the products have good performance. If the stacking activation curing process is not ideal, the characteristics of the product are long setting time and reduced strength, which cannot meet the technical requirements of cement production. For this reason, the stacking activation curing process adopted is 72-120 hours at minus 5 degrees and 36-72 hours below 40 degrees under natural conditions. Since the high and low curing temperature and the length of time have a great relationship with the setting time and strength of the product, according to actual needs, the stacking activation curing temperature is determined to be minus 5 degrees and below 40 degrees as the stacking activation curing temperature, and the optimal curing time is 36-120 hours, so that a certain amount of green low-carbon phospho-gypsum accelerator products with high crystal density and activity are formed.
[0019] Preferably, the rolling stirring pressure is 3-5 MPa, the rotation speed is 200-208 rpm, and the time is 2-3 min.
[0020] Preferably, the stacking temperature is -5 to 40°C and the stacking time is 36 to 120 hours.
[0021] The third aspect of the present invention provides an application of the above-mentioned green low-carbon phospho-gypsum setting accelerator or the green low-carbon phospho-gypsum setting accelerator prepared by the above-mentioned preparation method in promoting cement coagulation and / or improving cement strength.
[0022] The fourth aspect of the present invention provides a method for promoting cement coagulation and / or improving cement strength, wherein the green low-carbon phospho-gypsum coagulant or the green low-carbon phospho-gypsum coagulant obtained by the preparation method is added to cement.
[0023] Preferably, the content of the green low-carbon phosphate gypsum accelerator is 6% to 7%.
[0024] Preferably, the cement is selected from one of silicate cement, ordinary cement, slag cement, fly ash cement, pozzolana cement and composite cement.
[0025] Compared with the prior art, the beneficial effects of the present invention include at least:
[0026] The phosphogypsum coagulant of the invention uses phosphogypsum waste slag discharged from phosphate fertilizer plants, waste slag aluminum ash discharged from aluminum industry and waste slag potassium carbonate discharged from potassium carbonate plants as raw materials, and obtains a green low-carbon phosphogypsum product with (K2SO4·CaSO4·H2O) and potassium sulphur aluminium as main active ingredients through mixing, rolling, stirring, stockpiling, activation and curing under natural conditions, thereby realizing resource utilization of solid waste materials, achieving a waste utilization rate of up to 100% and zero carbon emission.
[0027] When the present invention uses phosphogypsum, aluminum ash and potassium carbonate waste residue as raw materials to prepare a green low-carbon phosphogypsum coagulant, the natural curing temperature is below -5 to 40°C, and high-temperature drying and adding of natural materials to treat the phosphogypsum are not required. The process is simple and the cost is low.
[0028] The green low-carbon phosphogypsum coagulant of the present invention directly replaces natural gypsum by 100% and is added to cement, which can improve the setting time and strength of cement. Specifically, the setting time of cement is advanced by 4-7 hours, and the strength is improved by 7.7-14.5MPa. In addition, the present invention uses solid waste materials as raw materials, solves the problem of the disposal of waste residue phosphogypsum, and avoids the pollution to the environment caused by the accumulation of solid waste materials. DETAILED DESCRIPTION
[0029] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0030] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.
[0031] The raw materials used in the following examples are as follows:
[0032] Phosphogypsum waste residue: particle size is 30.6um, from Anhui Tongling Phosphate Fertilizer Co., Ltd.;
[0033] Aluminum ash: particle size is 18.2um, from Shandong Aluminum Industry Co., Ltd.;
[0034] Potassium carbonate waste residue: particle size 15.5um, from Huaian Jingshen Chemical Co., Ltd.;
[0035] Portland cement: Model P·I52.5, from Xuyi Langshan Cement Co., Ltd.;
[0036] Ordinary cement: Model P·O52.5, from Xuyi Langshan Cement Co., Ltd.;
[0037] Slag cement: Model P·S·A52.5, sourced from Xuyi Langshan Cement Co., Ltd.;
[0038] Fly ash cement: model P·F52.5, sourced from Xuyi Langshan Cement Co., Ltd.;
[0039] Pozzolan cement: model P·P52.5, sourced from Xuyi Langshan Cement Co., Ltd.;
[0040] Composite cement: Model P·C52.5, sourced from Xuyi Langshan Cement Co., Ltd.
[0041] Example 1
[0042] This embodiment is a green low-carbon phospho-gypsum coagulant, characterized in that the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0043] Phosphogypsum waste slag 95%, aluminum ash 2% and potassium carbonate waste slag 3%.
[0044] The preparation method of the above-mentioned green low-carbon phosphite gypsum coagulant comprises the following steps:
[0045] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0046] (b) rolling and stirring the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphite accelerator, wherein the rolling and stirring pressure is 5 MPa, the rotation speed is 208 rpm, and the time is 3 minutes; the stacking temperature is -5°C, and the time is 120 hours.
[0047] Example 2
[0048] This embodiment is a green low-carbon phospho-gypsum coagulant, characterized in that the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0049] Phosphogypsum waste slag 96%, aluminum ash 3% and potassium carbonate waste slag 1%.
[0050] The preparation method of the above-mentioned green low-carbon phosphite gypsum coagulant comprises the following steps:
[0051] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0052] (b) rolling and stirring the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphite gypsum coagulant, wherein the rolling and stirring pressure is 3 MPa, the rotation speed is 200 rpm, and the time is 2 min; the stacking temperature is 0° C., and the time is 72 h.
[0053] Example 3
[0054] This embodiment is a green low-carbon phospho-gypsum coagulant, characterized in that the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0055] Phosphogypsum waste slag 97%, aluminum ash 1.5% and potassium carbonate waste slag 1.5%.
[0056] The preparation method of the above-mentioned green low-carbon phosphite gypsum coagulant comprises the following steps:
[0057] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0058] (b) rolling and stirring the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphite accelerator, wherein the rolling and stirring pressure is 4 MPa, the rotation speed is 205 rpm, and the time is 3 min; the stacking temperature is 5° C., and the time is 72 h.
[0059] Example 4
[0060] This embodiment is a green low-carbon phospho-gypsum coagulant, characterized in that the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0061] Phosphogypsum waste slag 98%, aluminum ash 1% and potassium carbonate waste slag 1%.
[0062] The preparation method of the above-mentioned green low-carbon phosphite gypsum coagulant comprises the following steps:
[0063] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0064] (b) rolling and stirring the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphate gypsum coagulant, wherein the rolling and stirring pressure is 3 MPa, the rotation speed is 208 rpm, and the time is 2 min; the stacking temperature is 40° C., and the time is 36 h.
[0065] Example 5
[0066] This embodiment is a method for promoting cement coagulation and / or improving cement strength, characterized in that the green low-carbon phospho-gypsum coagulant of embodiment 1 is added to cement;
[0067] The content of the green low-carbon phosphorus gypsum accelerator is 7%;
[0068] The cement is silicate cement.
[0069] Example 6
[0070] This embodiment is a method for promoting cement coagulation and / or improving cement strength, characterized in that the green low-carbon phospho-gypsum coagulant of embodiment 2 is added to cement;
[0071] The content of the green low-carbon phosphorus gypsum accelerator is 6%;
[0072] The cement is slag cement.
[0073] Example 7
[0074] This embodiment is a method for promoting cement coagulation and / or improving cement strength, characterized in that the green low-carbon phospho-gypsum coagulant of embodiment 3 is added to cement;
[0075] The content of the green low-carbon phosphorus gypsum accelerator is 6%;
[0076] The cement is ordinary cement.
[0077] Example 8
[0078] This embodiment is a method for promoting cement coagulation and / or improving cement strength, characterized in that the green low-carbon phospho-gypsum coagulant of embodiment 4 is added to cement;
[0079] The content of the green low-carbon phosphorus gypsum accelerator is 7%;
[0080] The cement is fly ash cement.
[0081] Comparative Example 1
[0082] This comparative example is a green low-carbon phospho-gypsum coagulant, characterized in that the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0083] Phosphogypsum waste slag 95%, aluminum ash 2% and potassium carbonate waste slag 3%.
[0084] The preparation method of the above-mentioned green low-carbon phosphite gypsum coagulant comprises the following steps:
[0085] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0086] (b) stirring and mixing the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphite accelerator, wherein the stirring speed is 208 rpm, the time is 3 minutes, and the stacking temperature is -5°C, and the time is 120 hours.
[0087] Comparative Example 2
[0088] This comparative example is a green low-carbon phospho-gypsum coagulant, characterized in that the green low-carbon phospho-gypsum coagulant is prepared from the following raw materials in percentage by weight:
[0089] Phosphogypsum waste slag 95%, aluminum ash 2% and potassium carbonate waste slag 3%.
[0090] The preparation method of the above-mentioned green low-carbon phosphite gypsum coagulant comprises the following steps:
[0091] (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture;
[0092] (b) rolling and stirring the mixture to obtain the green low-carbon phosphate gypsum coagulant, wherein the rolling and stirring pressure is 5 MPa, the rotation speed is 208 rpm, and the time is 3 minutes.
[0093] Experimental example
[0094] In order to illustrate the effect of the green low-carbon phosphogypsum coagulant product of the present invention, the green low-carbon phosphogypsum coagulant products of Examples 1 to 4 of the present invention and Comparative Examples 1 to 2, as well as natural gypsum and phosphogypsum waste residue, were added to different cement products respectively; then samples were taken respectively and product quality tests were performed according to the GB / T175-2023 general cement inspection standard; the corresponding conditions of different phosphogypsum coagulants and cements and the test results are shown in Tables 1 and 2;
[0095] Table 1
[0096]
[0097]
[0098]
[0099] Table 2
[0100]
[0101]
[0102]
[0103] From Table 2, we can see that:
[0104] The green low-carbon phosphorus gypsum coagulant of the present invention directly replaces natural gypsum by 100% and is added to cement, which can improve the setting time and strength of cement. In addition, compared with the comparative example, the embodiment of the present invention can better improve the mechanical properties of cement.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A green low-carbon phosphorus gypsum coagulant, characterized in that: The green low-carbon phosphorus gypsum coagulant is prepared from the following raw materials in percentage by weight: Phosphogypsum waste residue 95% to 98%, aluminum ash 1% to 4% and potassium carbonate waste residue 1% to 4%.
2. The green low-carbon phosphate gypsum coagulant according to claim 1, characterized in that: The particle size of the phosphogypsum waste residue is 10 to 50 um; the particle size of the aluminum ash is 10 to 30 um; and the particle size of the potassium carbonate waste residue is 5 to 20 um.
3. The method for preparing the green low-carbon phospho-gypsum coagulant according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (a) weighing and mixing the raw materials according to their weight percentage to obtain a mixture; (b) rolling and stirring the mixture, and then stacking it for a period of time to obtain the green low-carbon phosphate gypsum coagulant.
4. The preparation method according to claim 3, characterized in that: The rolling and stirring process has a pressure of 3-5 MPa, a rotation speed of 200-208 rpm, and a time of 2-3 min.
5. The preparation method according to claim 3, characterized in that: The stacking temperature is -5 to 40°C and the stacking time is 36 to 120 hours.
6. Use of the green low-carbon phospho-gypsum coagulant described in any one of claims 1 to 2 or the green low-carbon phospho-gypsum coagulant prepared by any one of the preparation methods of claims 3 to 5 in promoting cement coagulation and / or improving cement strength.
7. A method for promoting cement coagulation and / or improving cement strength, characterized in that: The green low-carbon phospho-gypsum coagulant described in any one of claims 1 to 2 or the green low-carbon phospho-gypsum coagulant prepared by any one of the preparation methods in claims 3 to 5 is added to cement.
8. The method for promoting cement coagulation and / or improving cement strength according to claim 7, characterized in that: The content of the green low-carbon phosphorus gypsum coagulant is 6% to 7%.
9. The method for accelerating cement coagulation and / or improving cement strength according to claim 1, characterized in that: The cement is selected from one of silicate cement, ordinary cement, slag cement, fly ash cement, pozzolana cement and composite cement.